A practical guide to toxicology and human health risk assessment - Robinson, Laura 1965-author (John Wiley & Sons, Inc, 2019)
"Provides a practical and easy-to-use guide to the applications of toxicology for risk assessment - Focuses on toxicological risk assessment of chemical and environmental compounds and includes real-life examples like pesticides, alcohol, and cigarettes and their impact on human health - Addresses the similarities and differences between USA and EU regulatory requirements Contains self-test questions and a summary of the key points in each chapter. Toxicologists, industrial hygienists, regulatory professionals, chemical risk assessors, forensic scientists, chemists, health and safety professionals, product safety workers; Medical and occupational health personnel who need to interpret toxicology data; Students studying toxicology or dealing with the topic in related disciplines, like forensic science, health, and medicine"-- Provided by publisher.